Studi Difusi Gadolinium Makrosiklik Pada Sel Kupffer Menggunakan Simulasi Monte Carlo Cell - Stcay Gillian Alehandra Gore; Adita Sutresno; Andreas Setiawan (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Contrast agents containing gadolinium (Gd) are classified into two types based on their molecular structure: linear and macrocyclic. The macrocyclic type is known for its enhanced stability, resulting in minimal release of Gd ions within the body. The distribution of macrocyclic Gd within the kupffer cells in the liver, undergoes a diffusion process. In this study aimed to investigate the diffusion mechanism of macrocyclic gadolinium in kupffer cells. It employs a simulation geometry model employing Monte Carlo Cell and a three-compartment experimental model. The kupffer cell model in the simulation was generated using Blender 2.93 application, consisting of three compartments, while the experimental model involved three compartments containing a NaCl solution. The simulation results revealed that kupffer cell membran densities of 1480 molekul/?m2, 2961 molekul/?m2, 4442 molekul/?m2, and 5922 molekul/?m2 exhibited respective half-lifes of 0.547 s, 0.261 s, 0.198 s, and 0.148 s. Furthermore, the experimental results indicated that the models with 100, 200, 300, and 400 holes displayed half-lives of 1720 s, 578 s, 530 s, and 240 s, respectively. Result this research shows that higher membrane density and more significant number of holes results in faster molecule diffusion.